(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, the concept of social policy, its meaning and purpose will be briefly discussed, and it is necessary to create a social environment and a social agreement based on the balance of various social interests with the help of mechanisms that ensure the improvement of the quality of life of all citizens and the satisfaction of the population’s vital needs in New Uzbekistan.